Découverte de la diversité des Monogènes (Plathelminthes) des poissons cypriniformes endémiques de la péninsule balkanique : nouvelles espèces de Dactylogyrus et commentaires sur leur phylogénie et les associations hôte-parasite dans un contexte biogéographique - Řehulková, Eva; Benovics, Michal; Šimková, Andrea (Parasite, 2020)
Seven new species of Dactylogyrus Diesing, 1850 (Dactylogyridae) are described from the gills of seven endemic species of cyprinoids (Cyprinidae, Leuciscidae) inhabiting the Balkan Peninsula: Dactylogyrus romuli n. sp. from Luciobarbus albanicus (Greece), Dactylogyrus remi n. sp. from Luciobarbus graecus (Greece), Dactylogyrus recisus n. sp. from Pachychilon macedonicum (Greece), Dactylogyrus octopus n. sp. from Tropidophoxinellus spartiaticus (Greece), Dactylogyrus vukicae n. sp. from Delminichthys adspersus (Bosnia and Herzegovina), Dactylogyrus leptus n. sp. from Chondrostoma knerii (Bosnia and Herzegovina), and Dactylogyrus sandai n. sp. from Telestes karsticus (Croatia). To delineate species boundaries, we used an integrative taxonomic approach combining morphological and genetic data. With these tools, we illustrate that some species of monogeneans considered as cryptic might be designated as pseudocryptic (morphologically similar, not easily differentiated) after a posteriori detailed morphological examination, as happened with D. romuli n. sp. and D. remi n. sp. Thus, for accurate species characterization, it is particularly important to acquire both morphological and molecular data from the same individual specimens, ideally along with illustrations of taxonomically important structures directly taken from hologenophores. Using phylogenetic reconstruction, we investigated the phylogenetic position of newly described Dactylogyrus species within Dactylogyrus species from Balkan cyprinoids with regard to morphological characteristics, host range, and geographical distribution.
Keywords: Animals; Trematoda; biodiverzita; paraziti; Phylogeography; druhová specificita; Host-Parasite Interactions; Balkánský poloostrov; máloostní; interakce hostitele a parazita; Species Specificity; Parasites; Phylogeny; Croatia; Chorvatsko; fylogeografie; Biodiversity; Balkan Peninsula; Cypriniformes; zvířata; fylogeneze